Perencanaa Perencanaan Pengembangan Terminal Penumpang Jetak Kecamatan Kaliwungu Kabupaten Kudus - Putra, Ilham; Hidayati, Nor; Saputro, Yayan Adi; Roehman, Fatchur (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
Basically, transportation is very necessary to facilitate all activities carried out by humans. The development of land transportation, such as the development of public transportation, is very rapid from year to year, this also requires development and progress in terminals as one of the road transportation infrastructure for loading and unloading people and/or goods, as is the case at Jetak Terminal, Kec. Kaliwungu District. Kudus is a type C passenger terminal, but along with the development of transportation, this terminal has changed its function to a type B terminal, so it is necessary to develop the terminal in terms of capacity and infrastructure. The method used in this research is to record the number plates of public transport entering, parking and leaving the terminal. Before conducting research, first ask for a research permit letter from the campus and the District Government. holy in this case BAPEDA Kab. Holy. The position of the Jetak Terminal in the existing road network system can be said to be quite strategic because it is on the main city route that connects Kaliwungu District with other areas, both in the western part of the city and with areas in the eastern part. Jetak Terminal has an area of ​​6.750 m², which consists of the building area and public transport parking area. Jetak Terminal currently has a parking area used by angkudes, microbuses, AKDP and motorbikes. Based on the results of calculations and survey results in the field, the need for parking space at the Jetak Terminal is currently unable to serve existing needs, where many microbuses are waiting for passengers outside the terminal. As a form of solving problems at the Jetak Terminal, it is possible to develop the terminal by optimizing the existing land around the terminal so that it can be utilized for the development of the Jetak Terminal. Keywords: Jetak Terminal, Capacity, Transportation